Pengaruh Personality Dan Spiritualitas Di Tempat Kerja Terhadap Kinerja Dosen Di Makassar - Badaruddin Badaruddin; Fatmasari Fatmasari (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
This research is intended as an academic effort to find out more about the performance of lecturers and the factors that influence it. Personality factor is the best factor used to predict employee performance. Another factor that affects performance is a factor related to the work environment, namely Workplace Spirituality. This study uses a quantitative approach and applies survey research to take samples and distribute online questionnaires as a data collection tool. All returned e-questionnaires were verified, and the number of final respondents used as research data was 178 lecturers. This amount is considered appropriate because it has fulfilled the requirements for the number of research samples. The data analysis technique used SPSS assistance. The results of the study indicate that increasing the capacity of the lecturer's personality in carrying out professional duties as a lecturer will have an impact on improving the performance of the lecturer. Likewise with the improvement of working environment conditions that are able to foster a meaningful feeling at work, a feeling of being connected to the community and the enforcement of institutional values ​​that are in line with the values ​​believed by lecturers will have an impact on improving the performance of lecturers